Pelaporan Transaksi Keuangan Mencurigakan Oleh Notaris Sebagai Pejabat Umum Dalam Penegakan Hukum Pidana - Krisna, Dw. Ngk. Gd. Agung Basudewa; Suyatna, I Nyoman (Acta Comitas : Jurnal Hukum Kenotariatan, 2022)
In this study, the main objective is to determine the role of a Notary as a public official in the enforcement of criminal law. This study applies a normative method, a statutory approach and a conceptual approach, the sources of legal materials used are primary legal materials and secondary legal materials. The results of this study indicate the role and authority of a Notary in providing authenticity to his writings about the agreements, actions, and decisions of the parties facing him. Because Notaries have other powers described in the Act as referred to in "Article 15 paragraph (3)", then this opens the opportunity to increase the role of Notaries. Notaries have an important role as reporting suspicious financial transactions in an effort to enforce criminal law which can be done non-electronically or electronically through the goAML application. This is contained in PP Number 43 of 2015 regarding the Reporting Party in terms of Preventing and Combating the Criminal Action of Money Laundering. This must be done by Notaries considering that there is an evaluation of compliance with reporting obligations for Notaries carried out by the Supervisory and Regulatory Agency and/or PPATK. In addition, the role of the Notary is very crucial in the enforcement of criminal law, especially regarding the crime of money laundering as regulated in Law Number 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering.